New-onset refractory status epilepticus due to autoimmune encephalitis after vaccination against SARS-CoV-2: First case report - Werner, Jana; Brandi, Giovanna; Jelcic, Ilijas; Galovic, Marian (Frontiers in Neurology, 2022)
Background: Vaccination against SARS-CoV-2 has been used frequently to limit the pandemic, but may rarely be associated with postvaccinal autoimmune reactions or disorders. Case presentation: We present a 35-year-old woman who developed fever, skin rash, and headache 2 days after the second SARS-CoV-2 vaccination with BNT162b2 (Pfizer/Biontech). Eight days later, she developed behavioral changes and severe recurrent seizures that led to sedation and intubation. Cerebral magnetic resonance imaging showed swelling in the (para-) hippocampal region predominantly on the left hemisphere and bilateral subcortical subinsular FLAIR hyperintensities. Cerebrospinal fluid analysis revealed lymphocytic pleocytosis (7cells/µl), normal protein, and immunoglobulin parameters. Common causes of encephalitis or encephalopathy such as viral infections, autoimmune encephalitis with well-characterized autoantibodies, paraneoplastic diseases or intoxications were ruled out. We made the diagnosis of new onset refractory status epilepticus (NORSE) due to seronegative autoimmune encephalitis. The neurological deficits improved after combined antiepileptic therapy and immunomodulatory treatment including high-dose methylprednisolone and plasma exchange. Conclusions: Although a causal relationship cannot be established, the onset of symptoms shortly after receiving a SARS-CoV-2 vaccine suggests a potential association between the vaccination and NORSE due to antibody-negative autoimmune encephalitis. After ruling out other etiologies early immunomodulatory treatment may be considered in such cases.